Contemporary Ethno-Religious Development Crises in Northern Nigeria with a Special Reference to Some States: Genesis, Implication, Impact and the Quest for Prospect - Kabir Mohammed; Usman Mu’azu Alhassan; Jibrin Ibrahim Gani; Abdullahi Mohammed (International Journal of Trends in Humanities, 2025)
A study has been conducted purely for the exploration of the remote and immediate factors that frequently lead to the outbreak of the studied subject matter in the region and period under review. In this study, a multitude number of published and unpublished sources have been put into use for appropriate historical reconstruction of some major obstacles associated with political, economic, social, tribal and religious aspects of the region and its populace with the sole aim of proffering an outstanding solution for the well- being of the Region, Nigerian state and society by and large. According to the report, the main causes of crises are unequal resource distribution, young political manipulation, abuse of religion teachings, corruption, unfair elections, and a decline in public confidence in the government. In order to further particular political, economic, and social goals, it contends that incidents such as the 1986 Kafanchan riots, the Maitatsine in Kano, the religious clashes in Jos, and the current Boko Haram insurgency were staged. However, it is also not out of place for the study to bring into light that the evolution of contemporary economic and commercial ideologies such as banditry and kidnapping for ransom are not only Islamically, inhumane, misleading, irreligious and forbidden by both Islam and Christianity (Abrahemic Religions), but also irrelevant, false claims, devastating in nature and too disastrous to humanity and globe at large. Other contributing factors which the study holds responsible for the outbreak of the crises include indigene-settler-dichotomy, failure of the traditional, religious leaders as well as relevant policy making bodies to rise to the responsibilities ahead of them. Strategies for the Northern Region and Nigeria's political, economic, social, and religious advancement are suggested in the study's conclusion. Important suggestions include adopting democratic ideals, promoting trust, equity, good governance, and equitable resource distribution. Additionally, it calls on Northern politicians, elites, and traditional leaders to confront important issues for the benefit of the country and the region.
Keywords: Crises; Ethno; Impact; Implication; Prospect; Religious; development